Evolocumab for early reduction of LDL-C levels in patients with acute ischemic stroke: a randomized controlled trial - Qiu, Xiaohui; Liang, Yeyuan; Wei, Yunfei; Lu, Mengru; Mei, Yujia; Tang, Shiting; Tang, Jian; Liang, Jinyu; Liang, Junli (Frontiers in Neurology, 2024)
BackgroundLow-density lipoprotein cholesterol (LDL-C) has been determined as an established risk factor for acute ischemic stroke (AIS). Despite the recommendation for in-hospital initiation of high-intensity statin therapy in AIS patients, achieving the desired target LDL-C levels remains challenging. Evolocumab, a highly effective and quickly acting agent for reducing LDL-C levels, has yet to undergo extensively exploration in the acute phase of AIS. The aim was to assess the LDL-C reduction efficacy and safety of early application of evolocumab during the in-hospital phase of AIS patients.MethodsAn unblinded, single-center, prospective randomized controlled trial involving hospitalized AIS patients was conducted in the Second Affiliated Hospital of Guangxi Medical University in China. Patients were randomly assigned 1:1 to receive evolocumab 420 mg every 4 weeks or not, on top of standard of care (SOC) treatment (atorvastatin 40 mg/day and ezetimibe 10 mg/day), administered in-hospital until after 8 weeks. The primary outcome was the absolute change of LDL-C levels and the rate of achieving targeted lipid control at 8 weeks.ResultsTotally, 120 patients were recruited from January 2023 to December 2023. Mean LDL-C levels decreased from 3.15 mmol/L to 0.85 mmol/L in the evolocumab group, and from 3.17 mmol/L to 2.22 mmol/L in the control group, with the difference in mean change from baseline was −1.37 [95% confidence interval (CI) = −1.70 to −1.04, p < 0.001] at week 8. The rate of patients achieving targeted LDL-C <1.4 mmol/L was 81.67% in evolocumab group as compared with 13.33% in control group. Adverse events were similar in both groups.ConclusionOur study indicated that evolocumab added to high-intensity statin and ezetimibe therapy resulted in substantial reduction in LDL-C levels in early AIS patients and was well tolerated.Clinical trial registrationClinicalTrials.gov, identifier NCT05697185.